2018
DOI: 10.1210/jc.2017-02532
|View full text |Cite
|
Sign up to set email alerts
|

FOS, a Critical Downstream Mediator of PGR and EGF Signaling Necessary for Ovulatory Prostaglandins in the Human Ovary

Abstract: The increase of FOS/activator protein 1 in human periovulatory follicles after hCG administration is mediated by collaborative actions of PGR and EGF signaling and critical for the upregulated expression of key ovulatory genes required for the rise in ovulatory PG in human granulosa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Significant downregulation of three membrane‐associated transporters was confirmed in IR‐cKO mice. The hCG‐ and PGR‐dependent organic anion transporter, Slco2a1 , contributes to prostaglandin synthesis and action in granulosa cells of ovulatory follicles in humans . The zinc transporter, Slc39a14 , is expressed in cumulus granulosa cells (CGCs) and is thought to regulate free intracellular zinc in mouse oocytes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant downregulation of three membrane‐associated transporters was confirmed in IR‐cKO mice. The hCG‐ and PGR‐dependent organic anion transporter, Slco2a1 , contributes to prostaglandin synthesis and action in granulosa cells of ovulatory follicles in humans . The zinc transporter, Slc39a14 , is expressed in cumulus granulosa cells (CGCs) and is thought to regulate free intracellular zinc in mouse oocytes .…”
Section: Resultsmentioning
confidence: 99%
“…The hCG-and PGRdependent organic anion transporter, Slco2a1, contributes to prostaglandin synthesis and action in granulosa cells of ovulatory follicles in humans. 49,50 The zinc transporter, Slc39a14, is expressed in cumulus granulosa cells (CGCs) and is thought to regulate free intracellular zinc in mouse oocytes. 51 Direct analysis of the amino acid transporter, Slc7a11, has primarily been limited to regulation of intracellular glutathione synthesis in neuronal tissue, but could play a similar role in FSH-and LH-dependent glutathione production in granulosa cells to support oocyte health.…”
Section: Ir-cko Mice Demonstrate Misregulation Of Gene Involved In mentioning
confidence: 99%
“…Interestingly, members of each of these families are strongly induced in peri-ovulatory granulosa cells and are known to participate in the ovulation pathway 3942 . Also noteworthy are the recent findings that the RUNX transcription regulating cofactor CBFb is required for ovulatory gene expression 43 and that PGR participates in peri-ovulatory induction of with AP-1 family members Fos, JunB and JunD 44 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the expression of this gene drastically increases in ovulatory follicles after administration of human chorionic gonadotropin (hCG). It is one of the key ovulatory genes required to increase the level of prostaglandins (PG) during ovulation in human granulosa cells (Choi et al 2018 ). Earlier reports indicate the presence of FOS transcripts in germinal vesicles (GV) and metaphase II (MII) oocytes (Regassa et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%